FAKTOR-FAKTOR YANG MEMENGARUHI CARING PERAWAT ICU DAN IGD : Literature Review - Mokhamad Dicky Ali Pranoto (2020)
Caring is one indicator to measure the quality of nursing services. Nurses are required to carry out maximum care, including ICU and emergency nurses who work in a stressful, dynamic, busy, and unpredictable environment. Several factors strongly influence ICU and ER nurses in providing maximum care to the patients. The purpose of the research is to study the factors that influence caring of ICU and ER nurses. This writing is a literature review study from existing evidence available in the Pubmed and Science Direct database and the search engine of Google Scholar. Fifteen journals meet the inclusion criteria of the study. The results show that seven articles discuss the factors that influence caring for the ER nurses, and six articles discuss the factors that influence caring for ICU nurses. Two other articles discuss the factors that influence both ICU and ER nurses. The analysis found that there are similar factors that influence the caring of ER and ICU nurses. Those factors are knowledge, skills, technology, emotional intelligence, are benefits, spirituality, communication, nursing supervision, length of work, and work environment. Job stress found statistically not significantly affecting both ICU and ER nurses. Conclusion: 15 factors were identified from 15 articles, which are divided into five major groups. Those are knowledge and skills, technology, characteristics of nurses, nursing management, and work stress.